1981
DOI: 10.1507/endocrine1927.57.7_974
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration of Serum Unconjugated. Estradiol, Estriol and Estetrol in Pregnant Women, and the Significance of These Hormones in Pregnancy

Abstract: Simultaneous determinations of unconjugated estradiol (E2), estriol (E3) and 15 alpha-hydroxyestriol (E4) levels in maternal serum were studied serially to ascertain the significance of these estrogens in the feto-placental unit. The samples of serum were collected serially from 25 normal and 44 abnormal pregnancies. In normal pregnancy, these estrogen levels increased throughout pregnancy, especially E3 and E4 nearing the term. In 15 cases of IUGR pregnancy (including 4 cases of perinatal death), E2 levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This implied significancy of estriol in evaluating placental and fetal growth as reported by Muraguchi et al [19]. …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This implied significancy of estriol in evaluating placental and fetal growth as reported by Muraguchi et al [19]. …”
Section: Discussionsupporting
confidence: 70%
“…These sex hormones are synthesized in placental tissue during gestation [5], and cholesterol is the precursor of both. Muraguchi et al have reported that estradiol indicates placental function, whereas estriol indicates placental and fetal function [19]. Zhu et al have reported that progestin inhibits the antioxidant effect of estradiol in the absence and presence of aortic endothelial cell culture [17, 18] and that this effect is similar to that observed in trophoblastic cell cultures [6].…”
Section: Discussionmentioning
confidence: 98%
“…Another study concluded altered adrenocortical function and reduced estriol levels in IUGR infants [34]. It has been suggested that E2 and E3 levels are normally restored in normal pregnancies but in IUGR, E2 levels get decreased which indicate decreased placental functioning [35]. Progesterone is a potent vasodilator as well as muscle relaxant and its concentration increases with pregnancy.…”
Section: Epidemiologymentioning
confidence: 99%